Perempuan Dan Terorisme: Resiliensi Istri Eks Napiter Di Solo Raya - Roudhotul Jannah; Zulkipli Lessy (KOLONI, 2024)
This article was created to see the burdens experienced by two wives of former Solo Terrorist Network convicts, ranging from economic burdens to mental burdens due to facing stigma from society. The Solo terrorist network is the largest terrorist network in Indonesia, almost every terrorist act in Indonesia is connected to the Solo terrorist network. The data source used is primary data in the form of interviews with the wives of ex-convicts. So far, studies on the Solo terrorist network have focused on the perpetrators, who were all men. However, no one has yet discussed the victim of the terrorist act, namely the wife of the former Solo network terrorist perpetrator. The results of this research show that the wife of an ex-convict experiences multiple burdens but must be forced to be strong because she has to be both father and mother to her children, she also inevitably has to be able to heal the mental wounds on herself and her children.